2005
DOI: 10.1590/s1676-06032005000200014
|View full text |Cite
|
Sign up to set email alerts
|

Aranhas sinantrópicas em três bairros da cidade de Salvador, Bahia, Brasil (Arachnida, Araneae)

Abstract: In order to evaluate which are the synanthropic spiders of Salvador and also to know if there exists any relationship between spider composition and time of urban occupation, this study analized 677 spiders, captured in three city neighbourhoods with different urbanization times: Santo Antonio Além do Carmo (300-400 years), Itapuã (100-300 years) and Pituba (less than 50 years). Sample size inside and outside of residences was calculated based on 10% district census and collections were carried out always by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 3 publications
0
8
0
7
Order By: Relevance
“…In our survey, it is to be noted that the exotic ant Monomorium pharaonis Linnaeus, 1958 was not recorded, nor either the spider Physocyclus globosus Taczanowski, 1874. We know that these species are frequent in the state of Bahia (M. pharaonis) and at Salvador (P. globosus), where they are easily found in house interiors (Delabie 1993, Delabie et al 1995, Brazil et al 2005, however, these sites were not sampled in this study. Despite the high incidence of exotic and synanthropic ants and spiders recorded, these species only represented 6% of the total species collected in the MRS (362 ant and spider species).…”
Section: Synanthropic and Exotic Speciesmentioning
confidence: 98%
“…In our survey, it is to be noted that the exotic ant Monomorium pharaonis Linnaeus, 1958 was not recorded, nor either the spider Physocyclus globosus Taczanowski, 1874. We know that these species are frequent in the state of Bahia (M. pharaonis) and at Salvador (P. globosus), where they are easily found in house interiors (Delabie 1993, Delabie et al 1995, Brazil et al 2005, however, these sites were not sampled in this study. Despite the high incidence of exotic and synanthropic ants and spiders recorded, these species only represented 6% of the total species collected in the MRS (362 ant and spider species).…”
Section: Synanthropic and Exotic Speciesmentioning
confidence: 98%
“…However, many spider species present a wide distribution and some species are capable to occupy synanthropic habitats (e.g. Brazil et al 2005). In the current study, 27 synanthropic species were recorded.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have shown that spiders in urban areas have synanthropic habits, living in peridomiciliary and intradomiciliary regions. 23,27 According to Diaz, 28 spider bites can usually be prevented by simple personal and domestic measures. Another possible reason for these results may be underreporting from rural areas, where the population has poor access to health services and information.…”
Section: Discussionmentioning
confidence: 99%